Cutting Forces, Chips Formation and Surface Roughness in Rock Cutting Using Negative Rake Angle - Hermawan, Yuni; Soenoko, Rudy; Irawan, Yudy Surya; Setyabudi, Sofyan Arief (Manufacturing Technology Journal, 2020)
This research pertains to rock cutting used negative rake angle. The parameters used are negative rake angles of 0o, -5o, -10o, -15o, -25o, -30o, and -40o. Negative rake angle is known to play an important role in rock machining. Negative rake angle produces more chips powder in front of the tool surface. The interaction between these particles affects the thrust force that suppresses the rock surface. A large thrust force generates hydrostatic pressure around the tooltip. According to the findings of this research, negative rake angle -25o leads to the largest thrust force and smallest surface roughness for 15.17 N and 1.21 ?m, respectively with smooth and uniform chips. The rock surface and the resulting chips powder was observed by scanning electron microscope (SEM) in order to prove the effect of hydrostatic pressure working on the tooltip. Meanwhile the hydrostatic pressure changed the brittle cutting mode into a brittle-ductile cutting mode.
Keywords: Rock cutting; Negative rake angle; Cutting force; Surface roughness